Banking Business in the Context of Measuring Employee Performance Based on Knowledge Management, Ability, Motivation, Islamic Economic Skills - Hermawan, Eric (International Journal of Social Science and Business, 2024)
From the standpoint of Islamic economics, this study seeks to ascertain how knowledge management, motivation, and skills affect worker performance. Employees at BSI KC Pandanaran in Semarang are the subject of this study. A causal research design was used to conduct this study with 108 respondents. This test was conducted using instrument testing with SPSS software and descriptive analysis as the analysis technique. According to the study's findings, knowledge management significantly affects workers' performance from an Islamic economic standpoint. From the standpoint of Islamic economics, skills play a major role in employee performance. Ability has a significant influence on how effectively employees perform from the standpoint of Islamic economics. Motivation has a big impact on how well employee’s work. Furthermore, knowledge management, skill, ability, and motivation have a significant impact on staff performance at BSI KC Pandanaran Semarang.